The pH of CO2-saturated water at temperatures between 308 K and 423 K at pressures up to 15 MPa - Peng,C; Crawshaw,JP; Maitland,GC; Martin,Trusler JP; Vega-Maza,D (The Journal of Supercritical Fluids, 2013)
Abstract We report pH measurements for CO2-saturated water in the pressure range from (0.28 to 15.3) MPa and temperatures from (308.3 to 423.2) K. Commercially available pH and Ag/AgCl electrodes were used together with a high pressure equilibrium vessel operating under conditions of precisely controlled temperature and pressure. The results of the study indicate that pH decreases along an isotherm in proportion to −log10(x), where x is the mole fraction of dissolved CO2 in H2O. The expanded uncertainty of the pH measurements is 0.06 pH units with a coverage factor of 2. The reported results are in good agreement with the literature in pressure ranges up to 16 MPa at temperatures below 343 K. An empirical equation has been developed to represent the present results with an expanded uncertainty of 0.05 pH units. We also compare our results with a chemical equilibrium model and find agreement to within 0.1 pH unit.